Adaptive learning systems and artificial intelligence in language learning - Katonáné Gyönyörű, Klára Ida (Gradus, 2025)
The integration of adaptive learning systems with the continuously developing applications supported by artificial intelligence (AI) introduces new solutions in language education. This study examines AI-powered solutions that facilitate language learning, highlighting key areas where AI-driven applications can effectively support both learners and educators. AI-based platforms, such as natural language processing applications, automatic speech recognition systems or virtual teachers provide interactive and engaging learning experiences while developing key language skills. The continuous development and spread of AI-based applications can lead to significant changes in language learning as well as language teaching methodology.